2012
DOI: 10.4103/2231-4040.101010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Caesalpinia bonduc seed coat extract for anti-inflammatory and analgesic activity

Abstract: In the present work, Caesalpinia bonduc seed coat extract (CBSCE) has been evaluated for anti-inflammatory and analgesic activity C. bonduc seeds have been attributed with anti-inflammatory and analgesic properties in the folklore medicine. Here in our study, we have tried to carry out the systematic evaluation of the seed coat extract of C. bonduc to substantiate these claims. C. bonduc seed coat was extracted with 95% ethanol and concentrated; further, the extract was screened for anti-inflammatory and analg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Kannur et al (2012) reported that the seed coat extracts of C. bonduc was more effective in controlling the inflammation. Cerqueira et al (2009) extracted, purified and characterized galactomannans from non-traditional sources.…”
Section: Resultsmentioning
confidence: 99%
“…Kannur et al (2012) reported that the seed coat extracts of C. bonduc was more effective in controlling the inflammation. Cerqueira et al (2009) extracted, purified and characterized galactomannans from non-traditional sources.…”
Section: Resultsmentioning
confidence: 99%
“…Potent anti-inflammatory activity of C. bonducella seed coat extract has been reported. [ 19 ] Autacoids are one of the most important mediators of inflammation. They sensitize the nerve ending for pain sensation and enhance the inflammatory mediators to be released at the site of insult.…”
Section: Discussionmentioning
confidence: 99%
“…aesalpinia bonducella L. plant ( fig.1) is also known as "fever nut", belongs to family caesalpiniaceae. [1][2][3] C. bonducella is a huge thorny shrub known to be a local of South India, Burma and Ceylon, especially along the ocean drift and up to 2500 ft. in hilly regions. 4 C. bonducella used as a herbal medicine derived from Kingdom: Plantae, Order: Febales, Family: Caesalpiniacaeae, Genus: Caesalpinia, Species: C. bonducella; Part used: Seeds (Fig.2) of C. bonducella commonly known as Kakachika, Karanja.…”
Section: Introductionmentioning
confidence: 99%